Apakah sinyal kinerja keuangan masih terkonfirmasi? : Studi empiris lembaga keuangan di PT. BEI - Yulita Setiawanta; Much Azizium Hakim (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
Many previous studies have stated that financial performance such as capital structure, company growth and profitability can influence the firm value. These results confirm the existence of signal theory in the activities of investors in the Indonesian capital market. Based on past studies, this study aims to prove the confirmation of the signal theory again. This research was conducted on issuers of financial and banking institutions that have been listed on the Indonesia Stock Exchange at the end of 2016, starting with the study period from 2014 to 2016. With purposive sampling, identification was conducted to determine the number of samples used and the authors obtained 17 issuers as samples. Data analysis technique uses multiple linear regression analysis.The results of this study prove partially that the capital structure, and profitability affect the firm value, but not for the growth of the company. Based on these findings it can be stated also that in the case of this study the signal theory was declared quite effective confirmed working on the sample companies in this study, especially in the observation period, This is reflected by two of the three variables that significantly influence to the firm value as a reflection of investor responses from signals that informed by the sample company.